Strategi Kebijakan Peningkatan Kemanfaatan Riset Berbasis Kebutuhan Masyarakat, Swasta, dan Industri pada UIN Raden Mas Said Surakarta - Priyo Sulistiyono, Tato (JURNAL ILMIAH GEMA PERENCANA, 2025)
This policy paper describes that universities have strategic role as research centers and academic studies, research results often do not have real impact on the needs of society, industry, and government. This phenomenon also occurs at State Islamic University (UIN) Raden Mas Said Surakarta, where the research conducted has not been fully utilized to answer local development issues. This study aims to formulate policy strategy to increase usefulness of research in line with the needs of society, industry, and government. Theoretically, results serve as academic reference, while practically they are used as the basis for research development planning policies that have a direct impact on solving real problems. The study used qualitative approach with primary data from Focus Group Discussion (FGD) with 30 UIN stakeholders and secondary data from relevant sources. The analysis was conducted with Analytical Hierarchy Process (AHP) scale 1-9 and descriptive, tested for validity through source triangulation, then analyzed with hybrid filtering approach: data-driven, rule-based, and expert judgment. This study recommends that Rector formulate competency-based HR development policies, build cross-sector research partnerships, formulate research selection policies based on theoretical and practical benefits, establish local big data and AI systems, and establish MoUs with stakeholders to ensure the urgency and relevance of research.